Auditory Hallucinations in Schizophrenia and Nonschizophrenia Populations: A Review and Integrated Model of Cognitive Mechanisms - Waters, Flavie (Oxford University Press, 2012)
While the majority of cognitive studies on auditory hallucinations (AHs) have been conducted in schizophrenia (SZ), an increasing number of researchers are turning their attention to different clinical and nonclinical populations, often using SZ findings as a model for research. Recent advances derived from SZ studies can therefore be utilized to make substantial progress on AH research in other groups. The objectives of this article were to (1) present an up-to-date review regarding the cognitive mechanisms of AHs in SZ, (2) review findings from cognitive research conducted in other clinical and nonclinical groups, and (3) integrate these recent findings into a cohesive framework. First, SZ studies show that the cognitive underpinnings of AHs include self-source-monitoring deficits and executive and inhibitory control dysfunctions as well as distortions in top-down mechanisms, perceptual and linguistic processes, and emotional factors. Second, consistent with SZ studies, findings in other population groups point to the role of top-down processing, abnormalities in executive inhibition, and negative emotions. Finally, we put forward an integrated model of AHs that incorporates the above findings. We suggest that AHs arise from an interaction between abnormal neural activation patterns that produce salient auditory signals and top-down mechanisms that include signal detection errors, executive and inhibition deficits, a tapestry of expectations and memories, and state characteristics that influence how these experiences are interpreted. Emotional factors play a particular prominent role at all levels of this hierarchy. Our model is distinctively powerful in explaining a range of phenomenological characteristics of AH across a spectrum of disorders.